Alveolar rhabdomyosarcoma infiltrating bone marrow at presentation: the value to diagnosis of bone marrow trephine biopsy specimens. Issue 9 (September 1992) - Reid, M M; Saunders, P W; Bown, N; Bradford, C R; Maung, Z T; Craft, A W; Malcolm, A J
Abstract : AIMS: To describe the histological appearances of bone marrow infiltrated with rhabdomyosarcoma at presentation and to determine their value in establishing the diagnosis. METHODS: Patients presenting over seven years in the northern health region of England with rhabdomyosarcoma were studied. Bone marrow aspirates and trephine biopsy specimens taken at presentation were examined. RESULTS: Seven of 32 patients with rhabdomyosarcoma had bone marrow infiltration, resulting in marrow failure in all cases, at diagnosis. The diagnosis was established in these seven by the typical cytological appearances and immunophenotype of the infiltrating cells (all seven patients) and cytogenetic abnormalities (three patients). Histological examination of the bone marrow showed a pseudoalveolar pattern with fibrous septal bands, enlarged vascular channels, and lack of cohesion of the tumour cells within the subdivided aggregates in all seven. In four cases multinucleate giant cells, often with peripherally sited nuclei, were found. CONCLUSIONS: These histological features of infiltrated marrow are so characteristic that the diagnosis of alveolar rhabdomyosarcoma can be made, or at least suspected, in many cases even without recourse to technically difficult and expensive further investigations. Bone marrow biopsy should be a routine part of the investigation of patients with bone marrow failure and will be of particular value in the diagnosis of those with disseminated alveolar rhabdomyosarcoma.